Experimental mode characterization o a tympanic membrane from time domain high speed digital holographic tests - Tang, Haimi; Furlong, Cosme; Cheng, Tao; García-Manrique-Ocaña, José Manuel; González-Herrera, Antonio (My University, 2021)
Recent experimental methods allow to obtain more accurate results of the tympanic membrane (TM) after acoustically induced motion. In this work, data from transient experiments carried out on a cadaveric human temporal bone are studied. A high-speed digital holographic (HDH) system was used to obtain the acoustically-induce transient displacement of TM surface. Based on the experimental data, the shape of the outer face of the TM is also determined. The paper presents preliminary methodology for the determination of mode shapes. They are compared with modal numerical simulation of the same TM by ANSYS software. Results correlation allow to qualitative identify mode shapes and identify the ranges of main frequencies directly from transient test. This is also used to help as a starting point of other parameters, as material properties, for the iterative time-domain numerical-experimental validation we are working with.
Keywords: Tímpano; Holografía en medicina; Método de los elementos finitos; Tympanic membrane; High-speed digital holographic; finite element model